2009
DOI: 10.1088/0022-3727/42/16/165105
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid multiwalled carbon nanotubes and trioxide tungsten nanoparticles for hydrogen gas sensing

Abstract: The WO3/multiwalled carbon nanotubes (MWNTs) hybrid films were fabricated by spin-coating on an alumina substrate. The structure, morphology, chemical composition and quality of the as-prepared WO3 nanoparticles, functionalized MWNTs and WO3/MWNTs hybrid films were studied by SEM, TEM, XRD, XPS, DLS and Raman spectroscopy methods. Results show that WO3 nanoparticles were nucleated on oxygenated functionalized MWNTs in hybrid suspension. After coating and annealing the films at 350 °C, the hybrid WO3/MWNTs film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Recently composites of semiconductors with MWCNTs have been reported [19][20][21][22][23]. It has been reported that MWCNTs could enhance photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently composites of semiconductors with MWCNTs have been reported [19][20][21][22][23]. It has been reported that MWCNTs could enhance photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It could be expected that derivation of novel applications of carbonaceous nanomaterials by integration with other technologies, such as sensor or quantum electronic technology, would cover much broader perspectives (Bittencourt et al, 2006;Espinosa et al, 2007;Balazsi et al, 2008;Hashishin, and Tamaki, 2008;Ghasempour and Zad, 2009). In this review, some typical examples of novel applications of carbonaceous nanomaterials are summarized.…”
Section: Novel Applicationsmentioning
confidence: 98%
“…We further compare S 80 and t R 80 of a Pd/SCBD WO 3 film with those of other nano H 2 sensors operating at T sen ≥ 200 • C [25][26][27][28][29][30][31][32][33][34][35]. Data are plotted in Fig.…”
Section: Sensor Response and Response Timementioning
confidence: 99%